HASIL BELAJAR IPS TERPADU DAN KEMAMPUAN BERPIKIR KRITIS ANTARA TSTS DENGAN GI - Leni Widiawati; Pujiati Pujiati; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study aimed to compare GI and TSTS model on learning achievement of Social Studies and critical thinking skills. The collection of data through observation, interviews, documentation and testing. Hypothesis testing using a t-test of two independent samples. The results showed an average of Integrated Social learning outcomes and critical thinking skills of students whose learning using learning TSTS model was higher than GI model. The average achievment of Social Studies with TSTS models was 80,322 and its increasing was 27,903 while 78,5 for GI models with an increasing 25,5. While the critical thinking skills of using TSTS model was 82,451 and 21,193 for its increasing and 77,5 for GI model with an increasing 20,3.Penelitian ini bertujuan membandingankan model pembelajaran TSTS dengan GI terhadap hasil belajar IPS Terpadu dan kemampuan berpikir kritis. Pengumpulan data melalui observasi, wawancara, dokumentasi dan tes. Pengujian hipotesis menggunakan t-test dua sampel independen. Hasil penelitian rata-rata hasil belajar IPS Terpadu dan kemampuan berpikir kritis siswa menggunakan model TSTS lebih tinggi dibandingkan model GI. Rata-rata hasil belajar IPS Terpadu model TSTS 80,322 dengan peningkatan 27,903 dan model GI 78,5 dengan peningkatan 25,5. Sedangkan kemampuan berpikir kritis model TSTS 82,451 dengan peningkatan 21,193 dan model GI 77,5 dengan peningkatan 20,3.Kata kunci: hasil belajar, berpikir kritis, GI, TSTS.